Process Consultation dan Leadership Effectiveness for New Strategies sebagai Metode Penetapan Prioritas Kerja: Studi Pengembangan Organisasi pada Tingkat Kelompok - Yuni Nirwanasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This organizational diagnosis study aimed to identify the main barriers to work effectiveness in the Psychological Assessment Material Development Subdivision and to formulate an appropriate group-level intervention. The study used a case-study design with a mixed data collection approach. Three employees participated in a 30-item Open System Model questionnaire covering goal clarity, task structure, group composition, team functioning, and performance norms. Data were complemented through participatory observations and semi-structured interviews. Questionnaire results indicated that team functioning obtained the lowest mean score (M = 3.00), followed by goal clarity (M = 3.08). Qualitative findings showed that employees managed planned targets alongside incidental assignments, while direct monitoring and routine coordination forums were limited. Information about additional workloads and work obstacles was not consistently shared, making it difficult for the group to determine which tasks should receive priority. Stream analysis identified the core problem as the absence of a shared strategy for setting work priorities. Based on this diagnosis, a two-stage intervention was designed. Process consultation was proposed to establish a common understanding of the problem and secure commitment to change. The Leadership Effectiveness for New Strategies (LENS) method was then designed as a structured forum for identifying assignments, generating alternatives, consolidating categories, and determining priorities.